Positive BCOR ITD high grade endometrial stromal sarcoma discovered after miscarriage - Jacob Kilgore; Robert Bowers; Krista Denning; Nadim Bou Zgheib (Elsevier, 2021)
We report a case of high-grade endometrial stromal sarcoma originally assumed to be a benign leiomyoma, with BCOR internal tandem duplicates resulting in BCOR overexpression. A 34-year-old female presented to the gynecologic oncology service for recent miscarriage attributed to a large leiomyoma. She reported symptoms of vaginal bleeding and abdominal pain. Myomectomy and tissue analysis was performed which revealed BCOR internal tandem duplicates and cyclin D1 positive high grade endometrial sarcoma. Definitive treatment for the sarcoma was performed with pelvic washings, robotic assisted total laparoscopic hysterectomy with bilateral salpingo-oophorectomy, omentectomy, and pelvic lymph nodes dissection. Negative margins were obtained along with negative lymph node and omental sections. Her sarcoma was staged pT1b (FIGO 1B). At follow up, patient reported no symptoms and was informed no further treatment was indicated. It is rare for high grade endometrial stromal sarcoma (HG-ESS) to present in a 34-year-old woman, though BCOR internal tandem duplicate (ITD) high grade endometrial stromal sarcoma is more common in younger women. This patient also had a unique finding in the pathology report, positive progesterone receptor (PR) expression, making this an interesting but difficult diagnosis.